Pengembangan Bata Ringan Berbahan Dasar Limbah Pengolahan Emas Tradisional dengan Penguat Eceng Gondok - Pangga, Dwi; Prasetya, Dwi Sabda Budi; Ahzan, Sukainil (IKIP Mataram, 2018)
[Title: Development of Lightweight Brick Based on Traditional Gold Processing Waste with Water Hyacinth Booster]. Research has been carried out on the manufacture of light brick made from gold processing waste with water hyacinth filler. The study was carried out by varying the direction of water hyacinth fiber as filler in light brick making. The direction of the filler is arranged in a horizontal, orthogonal and random direction. In each filler direction, the percentage variation of water hyacinth is arranged with the volume fraction 0%, 15%, 30%, 45%, 60%, from the total volume of the amount of light brick. The test results show that in the horizontal fiber direction the compressive strength is (2.43; 0.25; 0.54; 0.24; 0.50) MPa with a density (1.62; 1.34; 1.58; 1.42; 1.25) gr /cm3. In orthogonal direction the compressive strength was (2.43; 0.26; 0.80; 0.63; 0.77) MPa with density (1.62; 1.42; 1.49; 1.53; 1.42) gr/cm3. While in the random direction the compressive strength was (2.43; 0.73; 0.69; 0.59; 0.65) MPa with a density (1.62; 1.20; 1.41; 1.13; 1, 20) gr/cm3. From these data by comparing with previous studies, the most stable compressive strength and density values are formed in orthogonal directions. While the density value is most formed in random direction. In all directions the compressive strength and stable density were formed in the 60% volume of filler. The test results show that the light brick that is formed into the category is very light (entered in 0.6 - 1.6 gr/cm3 range) and floating in water, with medium compressive compressive strength.